Deformation effects on isospin mixing and isobar analogue resonance for 74-80Kr isotopes - Aygör, Hasan; Ünlü, S.; Çakmak, N.; Selam, C. (Versita, 2014)
Pyatov's method has been applied to investigate Fermi beta transitions in deformed 74-80Kr isotopes. This self-consistent method, which was used to study the isobar analogue states in the spherical odd-odd nuclei, has to date not been applied for the isobar analogue states in deformed nuclei. The nucleon-nucleon residual interaction has been included so that the broken isospin symmetry in the mean field approximation has been restored and the strength parameter of the effective interaction has been taken out to be a free parameter. The energies and wave functions of the isobaric analogue excitations in 74-80Rb isotopes have been obtained within the framework of the pnQRPA method. The probability of the isospin mixing in the ground states and the centroid energies of the isobar analogue resonance have been presented and the deformation effects on these quantities have been quantified. © 2014 Versita Warsaw and Springer-Verlag Wien.
Keywords: isospin symmetry; pnQRPA